Determinan Non-Performing Loan (NPL) Perbankan Kawasan ASEAN - Rohadi, Sigit Catur; Sarumpaet, Susi; Syaipudin, Usep (Owner : Riset dan Jurnal Akuntansi, 2024)
There are numerous factors that influence Non-Performing Loan (NPL) in the banking sector. This research aims to examine empirical evidence regarding factors affecting NPL, namely GDP Growth, inflation, reference interest rates, loan growth, Capital Adequacy Ratio (CAR), and Current Account Saving Account (CASA). The novelty of this research is proposing CASA as a new independent variable influencing NPL. Population of this research comprises all banks listed in the Forbes Global 2000 released in May 2022, located within ASEAN countries, and possessing financial information relevant to variables at the study period. The data were processed using panel data regression, using Fixed Effect Model. This research finds that, GDP Growth, CAR, and CASA were not proven to have a significant impact on NPL. However, inflation, central bank interest rates, and loan growth were found to have a negative impact on NPL. This study contributes primarily to monetary authorities in the ASEAN region.